Splenic trauma: WSES classification and guidelines for adult and pediatric patients - Coccolini, Federico; Montori, Giulia; Catena, Fausto; Kluger, Yoram; Biffl, Walter; Moore, Ernest E.; Reva, Viktor; Bing, Camilla; Bala, Miklosh; Fugazzola, Paola; Bahouth, Hany; Marzi, Ingo; et al. (World journal of emergency surgery, 2017)
Spleen injuries are among the most frequent trauma-related injuries. At present, they are classified according to the anatomy of the injury. The optimal treatment strategy, however, should keep into consideration the hemodynamic status, the anatomic derangement, and the associated injuries. The management of splenic trauma patients aims to restore the homeostasis and the normal physiopathology especially considering the modern tools for bleeding management. Thus, the management of splenic trauma should be ultimately multidisciplinary and based on the physiology of the patient, the anatomy of the injury, and the associated lesions. Lastly, as the management of adults and children must be different, children should always be treated in dedicated pediatric trauma centers. In fact, the vast majority of pediatric patients with blunt splenic trauma can be managed non-operatively. This paper presents the World Society of Emergency Surgery (WSES) classification of splenic trauma and the management guidelines.